EMPLOYEE PERFORMANCE IMPROVEMENT MODELS - Rahmasari, Mei Rista; Wulansari, Nury Ariani (Management Analysis Journal, 2020)
The purpose of this research is to know the direct effect of work engagement, emotional intelligence, deep acting, and surface acting on employee performance. The population of this research is employees of 4 (four) BUMN Insurance companies in Semarang. The sampling technique used saturated sample technique and the number of samples are 121 employees. Methods of Data aollection used observation, interviews and questionnaires that were measured using a Likert scale. Methods of analysis of this study used the software of SPSS version 21. The results show that work engagement and emotional intelligence, respectively, had a significant positive effect on employee performance. Another case, with deep acting that does not show a significant effect on performance, while acting surface shows a negative effect on employee performance. The Conclusions of this study are optimal emotional intelligence will improve deep acting, surface acting, and work engagement roomates Ultimately Affects employee performance. Suggestions for companies to pay more attention to the emotional management capabilities of employees so that it does not Become a burden for employees. In addition to providing training in handling customers appropriately, and creating a comfortable working environment to support the expected emotional control in accordance with company requirements.